How does Learning Drama Help Students to Build Seven Survival Skills? - Een Nurhasanah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to answer the question how does drama learning help students develop the Seven Survival Skills? The method used in the research is the qualitative approach used in this study to describe in detail. The researcher uses the theory "Seven Survival Skills." They are as follows (Wagner, 2012): 1) Critical thinking and problem-solving; 2) Collaboration across networks and influence; 3) Agility and adaptability; 4) Initiatives and entrepreneurship; 5) Accessing and analyzing information; 6) Effective oral and written communication; 7) Curiosity and imagination. According to the findings of the study, drama can help people learn seven important survival skills by engaging in learning and dramatic activities. Several studies using drama learning activities have demonstrated the impact of theorizing about drama on students' ability to develop survival skills.